Ckip-1 3′-UTR Attenuates Simulated Microgravity-Induced Cardiac Atrophy - Zhao, Yinglong; Zhong, Guohui; Du, Ruikai; Zhao, Dingsheng; Li, Jianwei; Li, Yuheng; Xing, Wenjuan; Jin, Xiaoyan; Zhang, Wenjuan; Sun, Weijia; Liu, Caizhi; Liu, Zizhong; et al. (Frontiers in Cell and Developmental Biology, 2022)
Microgravity prominently affected cardiovascular health, which was the gravity-dependent physical factor. Deep space exploration had been increasing in frequency, but heart function was susceptible to conspicuous damage and cardiac mass declined in weightlessness. Understanding of the etiology of cardiac atrophy exposed to microgravity currently remains limited. The 3′-untranslated region (UTR) of casein kinase-2 interacting protein-1 (Ckip-1) was a pivotal mediator in pressure overload-induced cardiac remodeling. However, the role of Ckip-1 3′-UTR in the heart during microgravity was unknown. We analyzed Ckip-1 mRNA 3′-UTR and coding sequence (CDS) expression levels in ground-based analogs such as mice hindlimb unloading (HU) and rhesus monkey head-down bed rest model. Ckip-1 3′-UTR had transcribed levels in the opposite change trend with cognate CDS expression in the hearts. We then subjected wild-type (WT) mice and cardiac-specific Ckip-1 3′-UTR-overexpressing mice to hindlimb unloading for 28 days. Our results uncovered that Ckip-1 3′-UTR remarkably attenuated cardiac dysfunction and mass loss in simulated microgravity environments. Mechanistically, Ckip-1 3′-UTR inhibited lipid accumulation and elevated fatty acid oxidation-related gene expression in the hearts through targeting calcium/calmodulin-dependent kinase 2 (CaMKK2) and activation of the AMPK-PPARα-CPT1b signaling pathway. These findings demonstrated Ckip-1 3′-UTR was an important regulator in atrophic heart growth after simulated microgravity.